Makna Kejahatan dan Perilaku Menyimpang dalam Kebudayaan Indonesia - Josias Simon Runturambi (Antropologi Indonesia, 2017)
Crime is a social phenomenon that normally occurs in a society. Some of crime and deviant behavior is motivated by social and cultural conditions of local communities. In today society crime is no longer something to be feared or avoided, it is now gaines popularity and more approachable. Crime grows in Indonesian day to day basis in reality. Criminology studies and learns the meaning of criminal behavior in the culture and people of Indonesia, or known as ethnographic study of crime, identifying and inventorying the types of crimes that are inherent in the religion system, language and social organization of local communities in Indonesia. Variety of meaning in discourse of crime and deviant behavior on the cultural history of Indonesia is a unique cultural treasures and can not disappear just like that, it could even be a reference establishment of local culture-based criminal policy.Keyword: Crime, Deviance, Local Culture, Meaning